Transcolonic Migration of Retained Epicardial Pacing Wires - Sara Gonzales; Hugh White; Juan Echavarria (Case Reports in Radiology)
Temporary epicardial pacing wires are associated with rare complications. Most of these occur in the chest. Even rarer are complications that occur within the abdomen. We report a case of migrating epicardial pacing wires entering the abdomen and penetrating the transverse colon found incidentally on colonoscopy in an asymptomatic patient.